Development of Slope Protection Scheme for Senggarang Coastal Embankment Against Erosion - Soiful Bahri, Nor Iman Fatihah; Yahya, Nur Faezah (Progress in Engineering Application and Technology, 2023)
Senggarang coastal embankment (SCE) is currently facing the risk of structure failure with the erosion activities keep on happening on the seaward side of the embankment slope. The seaward side of slope structure has been exposed to unprecedented rate of tidal assault causing it to require constant repair and reinforcement in severe cases. Therefore, PLAXIS 2D software is used for numerical analysis of Senggarang embankment model simulation, where the existing riprap slope protection is analysed further with three different water level to examine the effect towards the embankment. Then, the study is continued with the simulation of the embankment model without any slope protection, cantilever retaining wall, and gabion retaining wall to get the result of total displacement, effective stresses, excess pore pressure, seepage analysis, and factor of safety. Each simulation is also implemented with geotextiles to check the effectiveness as underneath layers for slope protection. From the results, it is found that gabion retaining wall with geotextiles gives proper protection more than the current riprap structure with safety factor of 3.6. Regardless, PLAXIS 2D helps in developing gabion retaining wall slope protection scheme while considering the sustainability towards the environment.